Interlinked Factor Markets and Allocative Efficiency: Evidence from Rural West Bengal, India (The Pakistan Development Review, 2011)
The issue of the implication of interlinkage of factor markets on the allocative efficiency level of the farm households deserves a special attention in the light of the controversy among two distinct schools of thought: the Neoclassical and the Marxist. An attempt has been made in the paper to measure allocative and cost efficiencies of the interlinked holding vis-à-vis a comparable group of non-interlinked holding in the framework of Data Envelopment Analysis. Empirical evidence establishes the Neo-classical proposition that interlinked factor markets can be considered as one of the “efficiency improving institutional change” in rural agrarian economy. JEL classification: D61, C87, Q14. Keywords: Interlinkage, Allocative Efficiency, Rural Credit, Data Envelopment Analysis